Cameroon and Boko Haram: Time to think beyond terrorism and security - Denis Tull (Stiftung Wissenschaft und Politik (SWP), 2015)
The terrorist organisation Boko Haram will determine Cameroon's medium-term domestic and security agenda. Together with an underestimated structural propensity to crisis and political conflict, this presents the country with a double challenge. The ability of Cameroonian state and society to master both is far lower than talk about this "regional anchor of stability" would have it. Europe should start developing ideas on crisis prevention. (SWP Comments)
Keywords: 320